KELUHAN MASYARAKAT PADA KEBIJAKAN PEMERINTAH DALAM PENGELOLAAN SAMPAH DI TPA SUMOMPO KOTA MANADO - PRICILIA CORELINA; MASJE PANGKEY; VERY LONDA (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to determine public complaints on government policies in waste managementat the Sumompo TPA Manado City. This study used qualitative research methods. The data analysistechnique carried out is data reduction, data presentation and conclusion drawing. There are six dimensionsof public complaints in the focus of the research, namely: 1) Response speed, 2) Facilities, 3) Repair, 4)Apology, 5) Credibility and 6) Attention. Based on the results of the research, the government has madevarious efforts to deal with waste management problems by paying attention to complaints from thecommunity, providing infrastructure assistance and making improvements as well as direct supervision ofthe waste management and reduction process, reducing complaints from the public.Keywords: Community Complaints, Policy, Waste Management